Moulding hydrodynamic 2D-crystals upon parametric Faraday waves in shear-functionalized water surfaces - Mikheil Kharbedia (Nature Portfolio, 2021)
There is a renewed interest in Faraday waves patterns in the field of nonlinear metamaterials due to their tunable templating capacity. Kharbedia et al. show that free-standing water surfaces with ordered patterns can be generated and controlled by the Faraday waves with help of stiffening surfactants.